A cidade de São Paulo e seus rios: uma história repleta de paradoxos - Isabel Cristina Moroz-Caccia Gouveia (Confins)
This article presents a brief historic report of the relation of the city of São Paulo with its rives, creeks and streams, in four different moments: the foundation of the Villa de São Paulo dos Campos de Piratininga in 1554 up to the third quarters of XIX century; from the end of the XIX century up to 1930 (City of Coffee); from 1930 to 1950 (Industrial City) and, from 1950, when the conurbation process started and gave rise to the metropolitan area of São Paulo, until the current days (The Megalopolis). The research, based on historiography and iconography, points out the importance of the rich river network for the foundation and establishment of the city and shows how throughout time and as the city expanded, these hydric resources were deteriorated and came to be seen as obstacles to the urban growth, becoming targets of interventions and transformations. Such interventions involved the suppression of rivers from the townscape of the city of São Paulo.